The effect of post-exercise, lower-limb passive heating on endurance performance, muscle and vascular function - KEVIN JOHN (2022)
Introduction: Chronic application of passive heating has been shown to enhance factors associated with aerobic metabolism. Likewise, post-exercise passive heating provides an attractive strategy to prolong the exercising stimulus and has shown to improve endurance performance in temperate conditions. It is typical to use hot water immersion, sauna baths, hot-water perfused suits or diathermy to provide the necessary thermal stimulus, thus confining the studies to laboratory settings and may prevent their real-world application. In light of the recent developments in personal heating garments, the current study aimed to develop a mobile, home-based lower-body passive heating system, which was applied in a post-exercise format. The primary aim of the study was to investigate the effect of four-weeks of post-exercise passive heating on markers of endurance performance in recreationally trained adults compared to routine endurance training. Methods: The study included 30 recreationally trained individuals, who were randomly allocated to post-exercise passive heating (PH, n = 16) or control group (CON, n = 14). The PH group wore the passive heating system immediately following training for 90-120 min/day, completing a total of 20 heating sessions across the four-weeks. The CON group continued with their normal training without passive heating. To characterise the endurance phenotype, hallmark endurance markers were assessed: maximal oxygen uptake, gas exchange threshold, pulmonary oxygen uptake kinetics and critical torque, with simultaneous near infrared spectroscopy, vascular assessment of brachial artery flow mediated dilation and venous blood sample collection for analysis of heat shock proteins, nitric oxide and vascular endothelial growth factors. All of the above-mentioned characteristics were assessed at three testing blocks; PRE, MID & POST, each separated by two-weeks. Changes between groups from PRE to POST were analysed using analysis of co-variance. Results: Resting brachial artery diameter (p = 0.002) and maximal vasodilatory diameter (p < 0.001) was significantly higher in PH compared to CON after four-weeks. There was no significant difference between or within group for markers of endurance performance. Finally, a significant slowing of phase II time constant (p = 0.02) was found in the PH group, whilst the CON group improved their critical torque–deoxygenation (p = 0.03) ratio relative to the PH group. Conclusion: The four-week, post-exercise passive heating approach used in the current study did not improve endurance performance. Despite some improvements in the components of systemic resting blood delivery, the nature of the intervention appeared to result in suppression of beneficial adaptations that would otherwise be anticipated with routine endurance training. This study signifies the need for better understanding the dose-response relationship when utilising dual adaptative stimuli (exercise + thermal) for the purpose of enhancing endurance performance among healthy, active individuals. Transference of fundamental training principles to the design of thermal interventions, such as consideration of thermal load and recovery, may help to individualise future approaches, and thereby increase the probability of beneficial heat-mediated adaptations.